2019
DOI: 10.18502/jovr.v14i3.4784
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness and Hemoglobin A1c Levels in Patients with Type 2 Diabetes Mellitus

Abstract: PurposeThe aim of this study was to assess the correlation of hemoglobin A1c (HbA1c) levels with choroidal thickness in patients with type 2 diabetes mellitus (DM) using spectral domain optical coherence tomography (SD-OCT).MethodsIn this prospective case series, 180 eyes from 90 patients with type 2 DM were classified into three study groups based on HbA1c values: group 1 included patients with good glycemic control (HbA1c ≤ 7%), group 2 included patients with moderate glycemic control (HbA1c between 7% and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
5
11
1
2
Order By: Relevance
“…Duration of diabetes was 10.31 ± 8.27 years in the NDR group and 14.65 ± 6.22 years in the DR group ( p = 0.002), but it did not correlate with FChT or CVI. This observation is in agreement with other reports, such as Torabi et al [ 31 ], but in contradiction with Hiroaki et al [ 32 ] or Niestrata-Ortiz et al [ 33 ], who observed choroidal changes occurring before the development of DR and progression with increasing duration of DM despite the absence of any DR or increased retinal thickness. As Tan et al reported, the duration and control of DM can lead to potentially confounded choroidal thickness measurements [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Duration of diabetes was 10.31 ± 8.27 years in the NDR group and 14.65 ± 6.22 years in the DR group ( p = 0.002), but it did not correlate with FChT or CVI. This observation is in agreement with other reports, such as Torabi et al [ 31 ], but in contradiction with Hiroaki et al [ 32 ] or Niestrata-Ortiz et al [ 33 ], who observed choroidal changes occurring before the development of DR and progression with increasing duration of DM despite the absence of any DR or increased retinal thickness. As Tan et al reported, the duration and control of DM can lead to potentially confounded choroidal thickness measurements [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…We have compared HbA1C values between groups, thinking that poor diabetic control with permanent high blood sugar levels could induce choroidal vascular damage, as previous studies reported [ 31 , 34 ]. We found no significant difference between NDR and DR groups concerning HbA1C values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since our study consists of pediatric type 2 DM patients, the duration of diabetes follow-up is approximately 4 years and this value is within the first 77 months of the study of Tavares Ferreria et al In addition, they reported that choroidal thickness was not associated with diabetes duration, blood glucose level, HbA1c, and mean arterial pressure [21]. Unlike our study Torabi H et al showed that the HbA1c level correlated with choroidal thickness in adults with type 2 DM patients and stated that as the HbA1c level increased, the choroidal thickness decreased [22]. Similar to our study, Ambiya V et al could not see a significant difference between the choroidal thickness of DM patients without retinopathy and the control group [23].…”
Section: Discussioncontrasting
confidence: 42%
“…The examination process is non-invasive, rapid, and highly reproducible, with promising clinical application. Choroid thickness has proven to be important in the diagnosis of various ophthalmologic and systemic diseases (Tan et al, 2016 ; Obis et al, 2018 ; Steiner et al, 2019 ; Torabi et al, 2019 ). Currently, the relationship between choroid thickness and disease is a research hotspot.…”
Section: Introductionmentioning
confidence: 99%